Control of disinfection by-products and biodegradable organic matter through biological treatment - Shukairy, H.; Miltner, R.; Summers, R. (Revue des sciences de l'eau / Journal of Water Science, 1992)
The optimal use of ozonation as a pretreatment process prior to biological treatment of Ohio River water was investigated at both the bench (batch) and pilot-plant (continuous flow) scale. The study focused on disinfection by-products (DBPs) and DBP precursor compounds and on the production of biologically stable water. Biotreatment was achieved using a bench-scale fixed-film reactor with sand acclimated to the raw Ohio River water.Ozonation was found to create a number of aldehydes, in particular formaldehyde, methyl glyoxal, glyoxal and acetaldehyde. With the exception of formaldehyde, a plateau in the aldehyde yield occurred at an ozone to total organic carbon (03/TOC) ratio of 0,7 mg/mg, while formaldehyde increased with increasing ozone dose. After biotreatment, the concentration of aldehydes were below 1 µg/1. Increasing ozone doses were also found to increase the assimilable organic carbon (AOC), by both NOX and P17 procedures, and the biodegradable dissolved organic carton (BDOC). The AOC values showed a maximum at about an 03/TOC ratio of 2 mg/mg, white the BDOC continued to increase with the highest ozone dose : an 03/TOC ratio of 2,8 mg/mg.Both ozonation and biotreatment were fond to decrease the chlorine demand by up to 75 % for ozonation and 55 % for biotreatment.Similar trends were found for the impact of ozonation and biotreatment on the precursor compounds for total organic halogen (TOX), total trihalomethanes (TTHMs) and total haloacetic acids (THAAs), as measured by the formation potential (FP) test : 12 mg/l chlorine, 7 days, 25 °C, 6.5-7.2 pH. An ozone dose of 0.4 03/DOC (mg/mg) decreased the TOXFP, TTHMFP and THAAFP by 28 %, 23 % and 33 %, respectively. Further increases in ozone only marginally increased the amount of the TOXFP and TTHMFP removed, white a maximum removal of 53 % of the THAAFP occurred at 03/DOC ratio of 0.87 mg/mg. Biotreatment of the nonozonated samples yielded 39 %, 38 % and 73 % removal of the TOXFP, TTHMFP and THAAFP, respectively. Biotreatment of the ozonated sample yielded a 30 to 50 % reduction in TOXFP and TTHMFP, while a constant level of 30 to 40 µg/l of THAAFP was achieved. Chloropicrin formation potential increased with ozone dose, but subsequent biotreatment reduced it to below 0.2 µg/l.Ozonation was Pound to oxidize chorine demand and the precursors for TOX, THM and HAAs. However, it created chloropicrin precursors, aldehydes and other biodegradable organic matter. Biotreatment was found to further reduce the chlorine demand, the precursors for TOX, THMs and HAAs and reduce the ozone created disinfection by-products.